Student Entrepreneurship in Indonesia: A Descriptive Analysis based on the Global University Students’ Spirit Survey (GUESSS) Research - Eko Suhartanto (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2024)
This study examines the entrepreneurial intentions and activities of Indonesian university students, drawing insights from the 2018, 2021, and 2023 GUESSS (Global University Entrepreneurial Spirit Students’ Survey) reports. Using 5,000 students’ quantitative data, this article shows the pattern of student entrepreneurship dynamics, which includes students’ career choice intention, nascent and active entrepreneurship along with the influence of gender, family entrepreneurial background, and the academic environment. This finding shows an increase in students who prefer to become entrepreneurs five years after graduation than when they have just graduated. The study also highlights gender disparities in entrepreneurial career choice intention, with males consistently showing higher intention than females. Further, the study underscores the influence of family entrepreneurial background and university entrepreneurial environment. Students from entrepreneurial families show a stronger intention toward entrepreneurship, while entrepreneurship education and support systems in universities foster a more conducive environment for student entrepreneurship. Keywords: student entrepreneurship, entrepreneurial intentions, university education